Manganese and trace element removal from New Zealand coal mine drainage using limestone leaching beds. Issue 2 (3rd April 2019) - Christenson, Hannah; Pope, James; Trumm, Dave; Newman, Nigel; Blanco, Ivan; Kerr, Gemma; Young, Mike; Uster, Ben
ABSTRACT: Limestone leaching beds are used in passive treatment systems to remove Mn(II) from mine drainage. Removal typically involves a combination of biotic and abiotic mechanisms. Six laboratory scale reactors were set up to examine the relative importance of different removal mechanisms of Mn. Duplicate reactors contained limestone, limestone with pyrolusite, and quartz. Acid mine drainage (AMD) containing 2 mg/l Mn, 0.3 mg/l Zn, and 0.08 mg/l Ni was fed in two streams to the duplicate sets of reactors, one stream was treated with biocide. Removal of Mn by limestone alone is minimal, and is enhanced by the presence of pyrolusite in a reactor. The most effective removal of Mn was achieved in the biotic limestone reactors, and microbial Mn (II) oxidation appears to be important for optimal removal of Mn from solution. Ni and Zn removal appeared coupled to Mn removal, likely due to their sorption onto Mn oxide surfaces.